An ethnographic study on the dietary differences in two generations - María Mercedes Rizo Baeza (Universidad de Alicante, 1998)
Dietary habits in human beings are one of the most evident ways to approach their cultural signs. When feeding, humans not only satisfy their biological needs but they express a means of social relationship. This study considers the different dietary habits of two generations. The study has been carried out in a particular area of the Alicante outskirts. Two different groups of people were given a card to record the day-to-day meals they had for a whole week. One group was of people over sixty and the other were children from two to fourteen years old. The study highlighted the different habits that exist between grandparents and grandchildren. The results have confirmed the hypothesis that children are easier influenced by external factors (means of communication, advertising, attractive wrappings...) than elderly people. Children prefer simpler food - plenty of sweet snacks rather than fish, fruit or vegetables which seldom appear in their in-take. On the other hand adults stick more to their cultural preference for traditional food.